Race, Trust in Police, and Mental Health Crisis Support. (August 2021) - Frankham, Emma; Jacobi, Christopher; Vaidyanathan, Brandon
This report examines police-public encounters that resulted in the fatal shooting of civilians during 2015 and 2016. How police contact was initiated varies by race/ethnicity, age, sex, mental health status, and whether (or how) the individual killed by police was armed with a weapon. This crucial information sheds further light on fatal police shootings.